The non-designer's Illustrator book : essential vector techniques for design - Williams, Robin, 1953- (Peachpit Press, 2012)
Many designers and photographers own the entire suite of Adobe creative products, but they manage to learn only one or two of the applications really well. This new addition to the popular Non-Designer's series from best-selling authors Robin Williams John Tollett includes many individual exercises designed specifically to teach the tools and features in Illustrator CS5.5 that designers (as opposed to illustrators) need to use. Along the way, the book offers many design tips for non-designers. Individual exercises ensure that a reader can jump in at any point and learn a specific tool or technique. In this non-designer's guide to Illustrator techniques, you'll learn: How vector images, as in Illustrator, are different from raster images, as in Photoshop, and when to choose which one How to use Illustrator CS5.5's tools to create and work with lines, shapes, anchor points and control handles, color, etc. How to draw your own shapes and trace others How to enter text and control the design of it How to take advantage of the symbol libraries, clipping masks, variable-width strokes, and much more When and why to rasterize elements of your vector image.